1994
DOI: 10.1128/iai.62.2.442-448.1994
|View full text |Cite
|
Sign up to set email alerts
|

M protein mediates streptococcal adhesion to HEp-2 cells

Abstract: Streptococcus pyogenes adheres to human epithelial cells in vitro and in vivo. To identify adhesins, cell wall components were extracted from S. pyogenes M6 with alkali or by treatment with mutanolysin and lysozyme. HEp-2 cells were incubated with extracts of S. pyogenes M6 and then analyzed by Western blot (immunoblot) assays, using antibodies to S. pyogenes. Only one streptococcal component (62 kDa) was bound to HEp-2 cells and was identified serologically as M6 protein. Experiments with pepsin-cleaved fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 46 publications
2
62
1
Order By: Relevance
“…M6 is the most abundant protein on the surface of JRS4, mediating GAS adherence to eukaryotic cells, but it is considerably less effective than protein F1 in mediating GAS entry into cells (Okada et al, 1994;Wang and Stinson, 1994;Jadoun et al, 1998;Berkower et al, 1999). In contrast to the polar distribution of protein F1, the distribution of M6 protein on the surface of the cocci chain was more homogeneous (compare Fig.…”
Section: Protein F1 Is Unevenly Distributed On Gas Surfacementioning
confidence: 97%
“…M6 is the most abundant protein on the surface of JRS4, mediating GAS adherence to eukaryotic cells, but it is considerably less effective than protein F1 in mediating GAS entry into cells (Okada et al, 1994;Wang and Stinson, 1994;Jadoun et al, 1998;Berkower et al, 1999). In contrast to the polar distribution of protein F1, the distribution of M6 protein on the surface of the cocci chain was more homogeneous (compare Fig.…”
Section: Protein F1 Is Unevenly Distributed On Gas Surfacementioning
confidence: 97%
“…Two variants of each type were analysed. The number of colony-forming units (cfu) from strains HW4 and HW8 decreased significantly during 3 h rotation in fresh phagocytic human blood ( High frequency invasion is not associated with more efficient adherence to A549 cells Adherence of some strains of group A streptococci to epithelial cells (Wang and Stinson, 1993) and keratinocytes (Okada et al, 1994) has been shown to require M protein. Experiments were performed to determine whether high-frequency internalization by LW variants relative to HW cultures reflected differences in their capacity to adhere to A549 cells.…”
Section: Colony Variants Differ In Their Capacity To Resist Phagocytosismentioning
confidence: 99%
“…The quantitatively dominating of these proteins, the M protein, has been traditionally regarded as a major virulence factor primarily through its ability to provide S. pyogenes with phagocytosis resistance [14,15]. However, the M protein is also likely to be involved in promoting bacterial adhesion to host tissue [16][17][18][19][20][21][22].…”
mentioning
confidence: 99%